Implementing Silent Disco Headphones in a Hospital Unit: A Qualitative Study of Feasibility, Acceptance, and Experience Among Patients and Staff - Lillian Hung, PhD, RN; Kevin Dahl, BMT; Gail Peake; Luka Poljak; Lily Wong; Jim Mann, LLD; Michael Wilkins-Ho, MD; Habib Chaudhury, PhD (SAGE Publishing, 2021)
Introduction Music is so widely available and inexpensive in the modern world; it is a common option for stress reduction, comfort and enjoyment. Silent disco headphones are used among young people; however, no study has yet investigated whether it is feasible to use these headphones to support mental health and well-being among older people with dementia in hospital settings. Objective The study's main objective is to explore whether music delivered by silent disco headphones was feasible and acceptable to a sample of inpatients staying in an older adult mental health unit of a large urban hospital. Methods We employed a video-ethnographic design in data collection, including conversational interviews and observations with video recording among ten patient participants in a hospital unit. A focus group was conducted with ten hospital staff on the unit. Results Our analysis identified three themes that represented experiences of patients and staff: (1) perceived usefulness, (2) perceived ease of use, and (3) attitude. Patient participants reported the music delivered by the headphones brought positive benefits. Witnessing the positive effects on patients influenced the staff's view of how music could be used in the clinical setting to support patients' well-being. Conclusions The music delivered by the silent disco headphones in an older adult mental health unit was found to be an acceptable and feasible intervention for patients. Leadership support is identified as an enabling factor in supporting technology adoption in the clinical setting. The findings can be used to inform practice development and future research.